ECONOMETRIC ANALYSIS OF FACTORS AFFECTING ENSURING ECONOMIC STABILITY OF CHEMICAL INDUSTRY ENTERPRISES (World Economics and Finance Bulletin, 2023)
In this paper have been investigated problems of ensuring the economic sustainability of industrial enterprises, developed a methodology for assessing the economic sustainability of industrial enterprises, analyzed the current state of the economic sustainability of industrial enterprises in our country, developed a methodology for ensuring the economic sustainability of industrial enterprises of the Republic of Uzbekistan, especially chemical industry enterprises, based on a deep study of the experience of advanced foreign countries, scientific proposals and practical recommendations for improvement are substantiated
Keywords: Chemical industry; enterprises; economic processes; stability of industrial complex